The Influence of Hospital Brand Image, Sharia Service Standards, and Psychospiritual Factors on Patient Loyalty in Indonesian Sharia Hospitals - Fatnan Setyo Hariwibowo; Maya Ariyanti; Maria Apsari Sugiat; Riski Taufik Hidayah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the impact of hospital brand image, Sharia service standards, and psychospiritual factors on patient loyalty in Sharia hospitals. Sharia hospitals in Indonesia are growing amid demand for Islam-aligned healthcare. Revenue and patients rise yearly but miss targets: 12-15 percent growth versus 20 percent goal, and 5-7 percent versus 15 percent. This signals loyalty issues involving brand image, Sharia quality, religiosity, trust, attitudes, and satisfaction. The aim is to analyze their interactions. Quantitative surveys with purposive sampling target patients from the past three years. Structural Equation Modeling analyzes 315 responses. Results reveal brand image drives Sharia standards; religiosity and trust form attitudes; standards and attitudes build satisfaction, the top loyalty predictor. Direct paths are significant; satisfaction variance is 53.1 percent, and loyalty 34.8 percent, via mediation. Improving brand and Sharia elements raises satisfaction and loyalty for growth targets. Prioritize digital marketing and spiritual care for retention.